A Comprehensive Systematic Review of The Effectiveness of Pharmacological Therapies For Osteoporosis in Males - Ayu, Putri; Khoirunnisa (International Medical Journal Corp. Ltd, 2024)
Background: Studies show that osteoporosis, a condition with low bone mineral density, increases the risk of fragility fractures, leading to higher mortality rates, disability, and increased healthcare expenses. Men are at higher risk, and pharmacological therapies have been found effective in reducing fracture risk, with zoledronate having the most significant effect on increasing lumbar spine bone mineral density. Methods: We conducted a search without sample size restrictions in the PubMed and Web of Science databases to find prospective studies on the effectiveness of pharmacologic therapies in men with osteoporosis. The analysis comprised a total of eight published prospective studies. Result: After a thorough three-step screening process, eight papers were determined to have pertinent connections to our current in-depth investigation. Following that, a close reading of the entire text was conducted, with additional attention being paid to these specific passages. Conclusion: Studies on osteoporosis treatments, such as alendronate, risedronate, zoledronic acid, ibandronate, denosumab, teriparatide abaloparatide, and romosozumab, show effectiveness in improving bone mineral density in men with the condition. However, evidence is limited due to unexplained differences.